Development and evaluation of 4WSS electric-driven chassis for high-clearance sprayer - He, Siwei; Shen, Yue; Zhang, Yafei; Liu, Hui (Frontiers in Plant Science, 2023)
The high clearance sprayer with conventional steering mechanisms, as an intelligent spraying machine, is frequently stuck or broken in muddy fields due to the excessive torque load. A Four-Wheel Self-Steering (4WSS) electric-driven chassis with a smaller turning radius and better passability is developed to handle complex agricultural terrains. The 4WSS chassis is mainly composed of two custom-designed steering bridges and four in-wheel drive motors. It can achieve steering and driving forward simultaneously through coordinate differential speed control of drive motors, saving a set of dedicated servo steering systems and requiring less torque during steering compared to conventional structures. A kinematic model depicting the speed relationships between four wheels is established via geometric analysis, and a Speed Distribution Controller (SDC) is designed to accomplish locomotion objectives.Experimental results demonstrate the effectiveness of the new prototype 4WSS chassis system in tracking speed and steering angle. Compared to conventional agricultural chassis, the 4WSS chassis has a smaller turning radius of 2877 mm. Furthermore, the 4WSS chassis exhibits superior performance in typical field conditions, including muddy terrain, deep gullies, and ridges.